2008
DOI: 10.1053/j.gastro.2008.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of mTOR Signaling in Hepatocellular Carcinoma

Abstract: BACKGROUND-The advent of targeted therapies in hepatocellular carcinoma (HCC) has underscored the importance of pathway characterization to identify novel molecular targets for treatment. Based on its role in cell growth and differentiation, we evaluated mTOR signaling activation in human HCC, as well as the anti-tumoral effect of a dual-level blockade of the mTOR pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
557
1
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 663 publications
(604 citation statements)
references
References 43 publications
16
557
1
12
Order By: Relevance
“…To note, it has been recently described that mTOR signaling has a critical role in the pathogenesis of HCC and that mTOR inhibitors have antineoplastic activity in experimental models of HCC. 39 Moreover, decreased autophagy in HCC correlates with a more aggressive cancer cell phenotype and poor prognosis. 21,40 Here we found that cannabinoid treatment reduces the growth of two different models of HCC subcutaneous xenografts in concert with decreased mTORC1 activation, enhanced AMPK phosphorylation and increased autophagy and apoptosis in those tumors.…”
Section: Discussionmentioning
confidence: 99%
“…To note, it has been recently described that mTOR signaling has a critical role in the pathogenesis of HCC and that mTOR inhibitors have antineoplastic activity in experimental models of HCC. 39 Moreover, decreased autophagy in HCC correlates with a more aggressive cancer cell phenotype and poor prognosis. 21,40 Here we found that cannabinoid treatment reduces the growth of two different models of HCC subcutaneous xenografts in concert with decreased mTORC1 activation, enhanced AMPK phosphorylation and increased autophagy and apoptosis in those tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactivation of mTORC1 have further been established for RCC cell lines and tumors as well as for various NET cell lines and animal models (Chan et al, 2010), and in B50% of hepatocellular carcinomas (Villanueva et al, 2008). Together, the observed exaggerated activation of mTORC1 in these LKB1/ AMPK/TSC-associated lesions suggests that mTORC1 would serve an effective target for therapy to treat these cancerous and hamartomatous lesions.…”
Section: Hyperactive Mtorc1 In Lkb1/ampk/tsc-associated Lesionsmentioning
confidence: 95%
“…Somatic inactivating mutations in the tumor suppressor gene PTEN are frequently detected in glioblastomas, melanomas, and in prostate and endometrial cancers (Sansal and Sellers, 2004). Loss of PTEN expression has been observed in sporadic hepatocellular carcinomas (Villanueva et al, 2008).…”
Section: Nf1mentioning
confidence: 99%
“…It may also have a role in leiomyosarcomas oncogenic processes, as it is the kinase responsible for AKT1 phosphorylation on serine 473, thus allowing its full activity. 16 RICTOR genomic gains have indeed been linked to tumor recurrence in hepatocellular carcinoma, 34 and its overexpression in glioma cell lines lead to increased anchorage-independent growth and motility. 35 Thus this study allowed us to demonstrate, in a large series of sarcomas with complex genomics, the frequent loss of PTEN expression in these tumors, presumably by a 'gene-dose effect' mechanism.…”
Section: Components Of the Mtor Complexes: Rictor Expressionmentioning
confidence: 99%